Supported nickel catalyst and method for catalyzing ethylene polymerization
Through the use of supported nickel catalysts, the problems of inconsistent molecular weight distribution, high branching degree and poor stability in UHMWPE preparation were solved, and ultra-high molecular weight polyethylene with narrow molecular weight, excellent mechanical properties and easy processing were achieved, which is suitable for large-scale production and high-end applications.
Patent Information
- Application Number
- CN202411356720.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-26
- Publication Date
- 2025-01-03
- Estimated Expiration
- 2044-09-26
AI Technical Summary
In the preparation of ultra-high molecular weight polyethylene (UHMWPE), existing catalysts have problems such as inconsistent molecular weight distribution, high branching degree, difficult processing and poor stability, which limits their wide application in high-end applications and industrial production.
Using a supported nickel catalyst, it is prepared by mixing alkyl magnesium, alkyl aluminum chloride and nickel complexes. By regulating the proportion and reaction conditions of aluminum, magnesium and nickel elements, it is prepared with excellent stability and high catalytic activity. Catalysts for catalyzing ethylene polymerization.
Ultra-high molecular weight polyethylene with narrow molecular weight distribution, low branching degree, excellent mechanical strength and easy processing are achieved, reducing polymer adhesion, improving the stability of the catalyst and the applicability of industrial production.
Smart Images

Figure CN119241747A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of ethylene polymerization, in particular to a supported nickel catalyst and a method for catalyzing ethylene polymerization. Background Art
[0002] Ultra-high molecular weight polyethylene (UHMWPE) generally refers to polyethylene with a molecular weight of more than one million. It has important value in many high-end application fields due to its excellent wear resistance, self-lubrication, chemical resistance and biocompatibility. In the process of preparing UHMWPE, the choice of catalyst has an important influence on the molecular weight and distribution of the polymer, the degree of branching, etc., and even determines the processing and mechanical properties of the polymer.
[0003] Early transition metals refer to transition metals with a smaller number of d electrons (generally no more than 5), such as scandium (Sc), vanadium (V), titanium (Ti), zirconium (Zr) and chromium (Cr); while late transition metals are those with a larger number of d electrons, such as manganese (Mn), iron (Fe), cobalt (Co), nickel (Ni), copper (Cu) and zinc (Zn).
[0004] Among the early transition metal catalysts, Ziegler-Natta (ZN) catalyst, which is translated into Chinese as Ziegler-Natta catalyst, is composed of triethylaluminum and titanium tetrachloride and is an excellent directional polymerization catalyst. Currently, commercial UHMWPE is usually prepared using Ziegler-Natta (ZN) catalyst. This type of catalyst has been widely used because of its long development time, low price, and ability to efficiently catalyze the polymerization of ethylene to produce UHMWPE. However, UHMWPE prepared by ZN catalyst has a wide molecular weight distribution. Although this is conducive to processing, it may lead to inconsistency in material properties and affect its performance in certain high-end applications. Other early transition metal catalysts can also catalyze the preparation of UHMWPE materials, but they often have the defect that there is basically no branching, which leads to processing difficulties. In addition, early transition metal catalysts generally have poor stability and are sensitive to water and oxygen, which is not conducive to industrial production.
[0005] In recent years, late transition metal catalysts such as α-diimine nickel have become a hot topic in the study of catalytic ethylene polymerization. They can produce UHMWPE with a narrow molecular weight distribution. However, the disadvantage is that the resulting polymers often have a high degree of branching, which may affect the crystallization and mechanical strength of polyethylene. In addition, in the process of preparing UHMWPE using homogeneous α-diimine nickel catalysis, the polymer easily adheres to the wall of the reactor, hindering mass transfer, resulting in material loss and difficulty in equipment cleaning, and seriously reducing the efficiency of the catalytic polymerization reaction. This limits its application in industrial production.
[0006] Therefore, it is of great significance to study and develop a catalyst for the preparation of UHMWPE products. Summary of the invention
[0007] In view of this, the technical problem to be solved by the present invention is to provide a supported nickel catalyst and a method for catalyzing ethylene polymerization, wherein the catalyst has excellent stability and is suitable for large-scale production and application. The use of the catalyst to catalyze ethylene can produce ultra-high molecular weight polyethylene with low branching degree, narrow molecular weight distribution, excellent mechanical strength and easy processing, and the sticking phenomenon is significantly reduced.
[0008] In order to achieve the above purpose, the technical solution adopted by the present invention is as follows:
[0009] The present invention provides a supported nickel catalyst, which is prepared by a mixed reaction of alkyl magnesium, alkyl aluminum chloride and a nickel complex shown in Formula 1;
[0010]
[0011] Wherein R and R' are independently selected from C1-C 10 Alkyl, C6-C 18 Aryl, C6-C 18 Heteroaryl, C1-C 30 Alkoxy, C2-C 30 Alkylamino, C6-C 30 Aryloxy, C6-C 30 Arylamino, C 10 -C 30 Aralkyl, C3-C 30 One or more of silanol, halogen, and nitro.
[0012] C1-C 10 Alkyl groups include, but are not limited to, methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl, tert-butyl, n-pentyl, neopentyl, hexyl, heptyl, octyl, nonyl, decyl, and the like.
[0013] The C6-C 18 Aryl groups include, but are not limited to, phenyl, naphthyl, benzyl, biphenyl, linear terphenyl, anthracenyl, phenanthrenyl, pyrenyl, fluorenyl, and the like.
[0014] The above reaction is simple and can be completed by dispersing the alkyl magnesium, alkyl aluminum chloride and the nickel complex shown in Formula 1 in a solvent.
[0015] In the above reaction, the alkyl magnesium and alkyl aluminum chloride generate a magnesium chloride carrier in situ.
[0016] The alkylaluminum chloride and the nickel complex shown in Formula 1 generate cationic nickel active species in situ.
[0017] The cationic nickel active species is supported on an in-situ generated magnesium chloride carrier.
[0018] The present invention does not impose any particular limitation on the manner of the above-mentioned loading, including but not limited to being embedded on the surface and / or inside of the in-situ generated magnesium chloride carrier.
[0019] The invention improves the performance of the catalyst by regulating the ratio of aluminum, magnesium and nickel elements in the raw materials for preparing the supported nickel catalyst.
[0020] Preferably, the molar ratio of the aluminum element to the nickel element in the alkylaluminum chloride and the nickel complex shown in Formula 1 is (200-1000):1; more preferably (300-1000):1;
[0021] Preferably, the molar ratio of the magnesium element to the nickel element in the alkyl magnesium and the nickel complex shown in Formula 1 is (10-500):1; more preferably (50-500):1; further preferably (200-500):1
[0022] Preferably, in the present invention, the molar ratio of aluminum element to magnesium element in the alkylaluminum chloride and alkylmagnesium is (1-10):1; more preferably (1-5):1; further preferably 2:1.
[0023] Preferably, the alkylaluminum chloride is selected from one or more of diethylaluminum chloride, dimethylaluminum chloride, ethylaluminum dichloride, dibutylaluminum chloride, methylaluminum dichloride, and sesquiethylaluminum chloride; more preferably diethylaluminum chloride, dimethylaluminum chloride, and sesquiethylaluminum chloride; further preferably diethylaluminum chloride.
[0024] Preferably, the alkyl magnesium is selected from dibutyl magnesium or diethyl magnesium; more preferably dibutyl magnesium.
[0025] The solvent for the above reaction is preferably one or more of dichloromethane, n-hexane, n-pentane, n-heptane and toluene; more preferably a mixed solvent of dichloromethane and n-hexane.
[0026] Preferably, the R and R' are independently selected from C1-C5 alkyl, C6-C 12 Aryl, C6-C 12 Heteroaryl, C1-C 10 Alkoxy, C2-C6 alkylamino, C6-C 30 Aryloxy, C6-C 20 Arylamino, C 13 -C 20 Aralkyl, C3-C 20 One or more of silanol, halogen, and nitro.
[0027] The C1-C5 alkyl group includes, but is not limited to, methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl, pentyl and the like.
[0028] The C6-C12 Aryl groups include, but are not limited to, phenyl, naphthyl, benzyl, biphenyl, and the like.
[0029] The C6-C 12 Heteroaryl groups include, but are not limited to, carbazolyl, indolyl, and the like.
[0030] The C2-C6 alkylamino group includes, but is not limited to, dimethylamino, diethylamino, diisopropylamino and the like.
[0031] The C 13 -C 20 Aralkyl groups include, but are not limited to, benzhydryl, trityl, and the like.
[0032] The C6-C 20 Arylamino groups include, but are not limited to, diphenylamino, dinaphthylamino, di(p-methylphenyl)amino, and the like.
[0033] Preferably, the nickel complex shown in Formula 1 has any of the following structures:
[0034]
[0035] In some specific embodiments of the present invention, the nickel complex represented by Formula 1 has any of the following structures:
[0036]
[0037] The present invention also provides a method for catalyzing ethylene polymerization, which uses the above-mentioned supported nickel catalyst to catalyze ethylene polymerization.
[0038] Preferably, the polymerization reaction temperature is ≤50°C; more preferably ≤15°C.
[0039] The polymerization reaction pressure is ≥10 bar; more preferably ≥20 bar.
[0040] Since the supported nickel catalyst of the present invention has good stability, it is possible to place the supported nickel catalyst in an ethylene polymerization device for a period of time before introducing ethylene, which solves the problem that the active catalyst has poor stability and cannot be stored for a long time and must react with the polymerization monomer in a timely manner.
[0041] The ultra-high molecular weight polyethylene obtained by the above-mentioned method of catalyzing ethylene polymerization has a branching degree of less than 5 branches per thousand carbon atoms;
[0042] The molecular weight distribution of the ultra-high molecular weight polyethylene is less than 3.5, and more preferably less than 3.0.
[0043] In some specific embodiments of the present invention, the weight average molecular weight of the ultra-high molecular weight polyethylene is 4.02 million or 3.98 million or 3.8 million or 3.6 million or 3.45 million or 2.88 million.
[0044] Compared with the prior art, the present invention provides a supported nickel catalyst prepared by a mixed reaction of alkyl magnesium, alkyl aluminum chloride and a nickel complex shown in Formula 1; wherein R and R' are independently selected from C1-C 10 Alkyl, C6-C 18 Aryl, C1-C 30 Alkoxy, C2-C 30 Alkylamino, C6-C 30 Aryloxy, C6-C 30 Arylamino, C 10 -C 30 Aralkyl, C3-C 30 One or more of silanol, halogen, and nitro. The supported nickel catalyst has excellent stability and high catalytic activity, and can be mass-produced and applied. The supported nickel catalyst of the present invention can be used to catalyze ethylene to obtain ultra-high molecular weight polyethylene with low branching degree, narrow molecular weight distribution, good mechanical properties, and easy processing without the phenomenon of sticking to the kettle. BRIEF DESCRIPTION OF THE DRAWINGS
[0045] Figure 1 This is the high temperature (110°C) H NMR spectrum of the polymer prepared in Example 1 ( 1 HNMR);
[0046] Figure 2 This is a high temperature (150° C.) gel permeation chromatography (GPC) spectrum of the polymer prepared in Example 1;
[0047] Figure 3 The differential scanning calorimetry (DSC) spectrum of the polymer prepared in Example 1 is shown in FIG. DETAILED DESCRIPTION
[0048] In order to further illustrate the present invention, the supported nickel catalyst and the method for catalyzing ethylene polymerization provided by the present invention are described in detail below with reference to the examples.
[0049] The polymerization reaction kettle can be carried out using a 200mL and 20L Swiss Buchi reactor or a 1L Beijing Century Senlang AC1000ml fully automatic reactor.
[0050] The polymerization solvent used is selected from n-hexane or toluene, both of which are from the solvent treatment system of Braun Company.
[0051] Example 1
[0052] (1) Preparation of nickel complexes
[0053] The nickel complex structure (R = -CH2Ph, R' = Me) is as follows:
[0054]
[0055] The preparation process of the above nickel complex is as follows:
[0056] 4-Methyl-2,6-dibromoaniline and pinacol diboron ester are subjected to a coupling reaction under palladium catalysis to obtain 4-methyl-2,6-bis(4,4,5,5-tetramethyl-1,3,2-dioxaborolane)aniline, which is subjected to a Suzuki coupling reaction with 1-benzyl-4-iodobenzene under tetrakis(triphenylphosphine)palladium catalysis (in a toluene / ethanol / water mixed solvent, at 90°C for 24 hours) to obtain 4-methyl-2,6-di(p-benzylphenyl)aniline.
[0057] The aniline and 2,3-butanedione were reacted in toluene at 80°C for 24 hours under the catalysis of p-toluenesulfonic acid, and then refluxed with water in a water separator for 3 days. The solvent was concentrated to remove the solvent, and the product was washed with methanol several times to obtain the target α-diimine ligand.
[0058] The ligand is reacted with an equivalent amount of (ethylene glycol dimethyl ether) nickel dibromide in dichloromethane for 3 days, the solvent is concentrated to remove, and the target nickel complex is obtained by recrystallization in a dichloromethane / n-hexane mixed solvent.
[0059] (2) Ethylene polymerization
[0060] First, the jacket temperature of the 20L reactor was set to 120°C and the reactor was vacuum dried. The temperature in the reactor was lowered to 15°C and maintained by circulating oil bath. Then 4.9L of hexane was added to the reactor.
[0061] Under a nitrogen atmosphere, diethylaluminum chloride (500 equivalents, 34 mL), dibutylmagnesium (250 equivalents, 17 mL), the above nickel complex (68 μmol, 78 mg) previously dissolved in dichloromethane, and 100 mL of n-hexane were mixed and stirred evenly to complete the in-situ loading process to obtain a loaded nickel catalyst which was loaded into an ampoule.
[0062] Under vacuum, the supported nickel catalyst in the ampoule was added into a 20 L reactor, and then ethylene was introduced, and the polymerization reaction was carried out while maintaining the pressure at 25 bar and 15° C. for 60 minutes.
[0063] After the polymerization was completed, the polymerization kettle was turned over to pour out the polymer after the reaction. Ethanol was added and stirred with a 1 mol / L hydrochloric acid solution for 120 minutes. The polymer was filtered and then dried in a vacuum oven to finally obtain 353 g of polymer, which was in a granular state and did not have the problem of sticking to the kettle.
[0064] Through high temperature 1 HNMR test (Bruker AV400 nuclear magnetic resonance instrument, using deuterated tetrachloroethane as solvent), the branching degree of the polymer was calculated to be about 1.7brs / 1000C ( Figure 1 ); High temperature GPC determination was performed at 150°C using PL-GPC 220 gel chromatograph with 1,2,4-trichlorobenzene as the mobile phase. The test showed that the Mw was about 4.02 million and the PDI was 2.22 ( Figure 2 ); The polymer melting point was tested by DSC3 or Q2000 differential scanning calorimeter at a scanning rate of 10°C / min and a scanning range of 50°C-180°C. Specifically, the melting point value of the second heating was 131.5°C ( Figure 3 The JJ-20 memory impact tester of Changchun Intelligent Instrument Equipment Co., Ltd. measured the simple supported beam unnotched impact strength of the obtained polymer to be 63.83 kJ / m 2 The cantilever beam impact strength was measured by the cantilever beam impact tester of Chengde Testing Machine Factory and was 64KJ / M 2 The density of the product tested by a true density meter is approximately 0.9177 g / cm 3 .
[0065] Stability verification experiment:
[0066] The process is the same as step (2) above, except that after the in-situ loading process is completed, the loaded nickel catalyst is added to a 20 L reactor at 15°C, stirred for 1 h in the absence of ethylene, and then ethylene is introduced for polymerization to obtain 332 g of polymer in a granular state without any reactor sticking phenomenon.
[0067] Because the supported nickel catalyst containing active centers is generated by mixing the diethylaluminum chloride, dibutylmagnesium and nickel complex of the present invention. Under normal circumstances, in the absence of ethylene, the active centers of the supported nickel catalyst are unstable, and leaving the catalyst for a period of time will lead to a significant decrease in activity. However, the above verification experiment shows that the supported nickel catalyst of the present invention is highly stable, and after being left for 1 hour, its activity decay is minimal.
[0068] Example 2
[0069] The same as Example 1, except that the structure of the nickel complex is as follows:
[0070]
[0071] The synthesis of the nickel complex is based on the route of the nickel complex in Example 1, except that 1-benzyl-4-iodobenzene is replaced by 1-diphenylmethyl-4-iodobenzene.
[0072] The ethylene polymerization reaction was carried out at 30°C, and 367 g of polymer was finally obtained. The polymer was in a granular state and there was no problem of kettle sticking.
[0073] Through high temperature 1 The branching degree of the polymer was calculated by HNMR test to be about 3.0brs / 1000C; the Mw of the polymer was determined by high temperature GPC to be about 3.45 million, and the PDI was 2.40; the melting point of the polymer was measured by DSC to be 130.5℃. The unnotched impact strength of the simply supported beam was 63.00kJ / m 2 . Izod double notch impact strength is 61KJ / M 2 .
[0074] The stability verification experiment was the same as that in Example 1. As a result, 358 g of polymer was obtained in a granular state without any sticking to the kettle.
[0075] Example 3
[0076] The same as Example 1, except that the structure of the nickel complex is as follows:
[0077]
[0078] The synthesis of the nickel complex is based on the route of the nickel complex in Example 1, except that p-methylaniline is replaced by p-fluoroaniline.
[0079] The ethylene polymerization reaction was carried out at 25°C, and 380 g of polymer was finally obtained. The polymer was in a granular state and there was no problem of kettle sticking.
[0080] Through high temperature 1 The branching degree of the polymer was calculated by HNMR test to be about 2.8brs / 1000C; the Mw of the polymer was determined by high temperature GPC to be about 2.88 million, and the PDI was 2.50; the melting point of the polymer was measured by DSC to be 131.2℃. The unnotched impact strength of the simply supported beam was 61.00kJ / m 2 . Izod double notch impact strength is 58KJ / M 2 .
[0081] The stability verification experiment was the same as that in Example 1. As a result, 333 g of polymer was obtained in a granular state without any sticking to the kettle.
[0082] Example 4
[0083] The same as Example 1, except that the structure of the nickel complex is as follows:
[0084]
[0085] The synthesis of the nickel complex is based on the route of the nickel complex in Example 1, except that p-methylaniline is replaced by p-methoxyaniline.
[0086] The ethylene polymerization reaction was carried out at 45°C, and 360 g of polymer was finally obtained. The polymer was in a granular state and there was no problem of kettle sticking.
[0087] Through high temperature 1 The branching degree of the polymer was calculated by H NMR test to be about 5.0 brs / 1000C; the Mw of the polymer was determined by high temperature GPC to be about 3.98 million, and the PDI was 2.70; the melting point of the polymer was measured by DSC to be 129.8°C. The unnotched impact strength of the simply supported beam was 58.00 kJ / m 2 . Izod double notch impact strength is 59KJ / M 2 .
[0088] The stability verification experiment was the same as that in Example 1. As a result, 355 g of polymer was obtained in a granular state without any sticking to the kettle.
[0089] Example 5
[0090] The same as Example 1, except that the structure of the nickel complex is as follows:
[0091]
[0092] The synthesis of the nickel complex is based on the route of the nickel complex in Example 1, except that 1-benzyl-4-iodobenzene is replaced by 1-(9-anthryl)-4-bromobenzene.
[0093] The ethylene polymerization reaction was carried out at 50°C, and 340 g of polymer was finally obtained. The polymer was in a granular state and there was no problem of kettle sticking.
[0094] Through high temperature 1 The branching degree of the polymer was calculated by HNMR test to be about 4.8brs / 1000C; the Mw of the polymer was determined by high temperature GPC to be about 3.8 million, PDI 2.30; the melting point of the polymer was measured by DSC to be 131.8℃. The unnotched impact strength of the simply supported beam was 55.00kJ / m 2 . Izod double notch impact strength is 52KJ / M 2 .
[0095] The stability verification experiment was the same as that in Example 1. As a result, 337 g of polymer was obtained in a granular state without any sticking to the kettle.
[0096] Example 6
[0097] The same as Example 1, except that the structure of the nickel complex is as follows:
[0098]
[0099] The synthesis of the nickel complex was carried out according to the method of CN 113045453 A and Example 1, wherein the bulky hindered aromatic amine was prepared by coupling 4-(9H-carbazole-9-yl)phenylboronic acid with 2,6-dibromo-4-methylaniline under palladium catalysis, and the remaining steps were completed according to the route of Implementation 1.
[0100] The ethylene polymerization reaction was carried out at 25°C, and 240 g of polymer was finally obtained. The polymer was in a granular state, and the problem of kettle sticking was alleviated compared with a homogeneous state.
[0101] Through high temperature 1 The branching degree of the polymer was calculated by H NMR test to be about 3.8brs / 1000C; the Mw of the polymer was determined by high temperature GPC to be about 3.6 million, and the PDI was 2.44; the melting point of the polymer was measured by DSC to be 130.0℃. The unnotched impact strength of the simply supported beam was 47.00kJ / m 2 . Izod double notch impact strength is 56KJ / M 2 .
[0102] The stability verification experiment was the same as that in Example 1. As a result, 200 g of polymer was obtained, which was in a granular state without any sticking to the kettle.
[0103] In summary, the supported nickel catalyst of the present invention has excellent stability and high catalytic activity, the prepared UHMWPE is in granular form, the kettle sticking phenomenon is significantly reduced and the processing performance is good.
[0104] The above embodiments are only used to help understand the method and core idea of the present invention. It should be noted that, for those skilled in the art, several improvements and modifications can be made to the present invention without departing from the principles of the present invention, and these improvements and modifications also fall within the scope of protection of the claims of the present invention.
Claims
1. A supported nickel catalyst, characterized in that It is prepared by mixed reaction of alkyl magnesium, alkyl aluminum chloride and the nickel complex shown in formula 1; Wherein R and R' are independently selected from C1-C 10 Alkyl, C6-C 18 Aryl, C6-C 18 Heteroaryl, C1-C 30 Alkoxy, C2-C 30 Alkylamino, C6-C 30 Aryloxy, C6-C 30 Arylamino, C 10 -C 30 Aralkyl, C3-C 30 One or more of silanol, halogen, and nitro.
2. The supported nickel catalyst according to claim 1, characterized in that The molar ratio of aluminum element to nickel element in the alkylaluminum chloride and the nickel complex shown in Formula 1 is (200-1000):
1.
3. The supported nickel catalyst according to claim 1, characterized in that The molar ratio of the magnesium element to the nickel element in the alkyl magnesium and the nickel complex shown in Formula 1 is (10-500):
1.
4. The supported nickel catalyst according to claim 1, characterized in that The molar ratio of aluminum element to magnesium element in the alkyl aluminum chloride and alkyl magnesium is (1-10):
1.
5. The supported nickel catalyst according to any one of claims 1 to 4, characterized in that The alkylaluminum chloride is selected from one or more of diethylaluminum chloride, dimethylaluminum chloride, ethylaluminum dichloride, dibutylaluminum chloride, methylaluminum dichloride, and sesquiethylaluminum chloride.
6. The supported nickel catalyst according to claim 1, characterized in that The alkyl magnesium is selected from dibutyl magnesium or diethyl magnesium.
7. The supported nickel catalyst according to claim 1, characterized in that The R and R' are independently selected from C1-C5 alkyl, C6-C 12 Aryl, C6-C 12 Heteroaryl, C1-C 10 Alkoxy, C2-C6 alkylamino, C6-C 30 Aryloxy, C6-C 20 Arylamino, C 13 -C 20 Aralkyl, C3-C 20 One or more of silanol, halogen, and nitro.
8. The supported nickel catalyst according to claim 1, characterized in that The nickel complex shown in Formula 1 has any of the following structures:
9. A method for catalyzing ethylene polymerization, characterized in that: The supported nickel catalyst according to any one of claims 1 to 8 is used to catalyze the polymerization of ethylene.
10. The method according to claim 9, characterized in that The polymerization reaction temperature is ≤50°C; The polymerization reaction pressure is ≥10 bar.
Citation Information
Patent Citations
Supported alpha-diimine compound and application of supported alpha-diimine compound in olefin polymerization
CN104804030A
Superimposed large-steric-hindrance alpha-diimine ligand, nickel catalyst, as well as preparation method and application thereof
CN111548285A
Large-steric-hindrance alpha-diimine ligand, nickel catalyst and preparation method and application thereof
CN112920300A
Rotation-limited superposed large-steric-hindrance alpha-diimine ligand, nickel catalyst, preparation method of alpha-diimine ligand, and application of nickel catalyst
CN113045453A
Late transition metal-supported catalyst, method for preparing the supported catalyst, and olefin polymerization method using the supported catalyst
KR1020100129981A